O demoníaco e a compulsão de destino: a apresentação do pacto fáustico em "Grande Sertão: Veredas" - Souza, Filipe Ramalheiro Venâncio de (2023)
The research investigates the demonic from the presentation of the Faustian pact in the novel ―Grande Sertão: Veredas. The demonic is a term that appears in literature expressively through the so-called Faustian tradition, which places it into question through the pact with the devil. The protagonists of the works that integrate such tradition perform the pact in an attempt to overcome a dilemma or engage in an impossible task. In ―Grande Sertão: Veredas, by João Guimarães Rosa, Riobaldo, the protagonist in the novel, makes the pact, which places him in a division against his desire. This division constitutes a problem concerning the sheer division of the psychic apparatus, in which the subject attributes demonic forces to something that, from his desire, is unrecognizable and even unbearable to consciousness. In light of this, our route was directed toward understanding the division implied in the demonic pact. According to it, what is unrecognizable by the subject is precisely because, at a moment before the constitution of the psychic apparatus, it has been refracted by it. However, this element returns to consciousness through the action of the death drive, which has the destiny compulsion as a borderline operating mechanism, causing the subject to attribute his acts to external agents, therefore demonic. This return is related to a remnant of the subject's idealized father figure, who is impossible to equate, returning to consciousness through the cruel commandments of the superego. At that point, we articulate Riobaldo‘s position concerning his father, taking into account the Lacanian contribution that divides him into different registers: symbolic, real, and imaginary, allowing it to illuminate significant problems in the debate on the developments that psychoanalysis has undertaken around the father figure, as well as clarifying Riobaldo‘s position in the pact based on his position about the constitutive division of the signifier. We next situate the protagonist‘s position before his desire, articulating the possibility of going ―beyond the father‖ to be able to access the singularity of his desire. The death of the character Diadorim at the end of the narrative allows Riobaldo to place it in the position of an object of desire when that becomes impossible. When the narrator encounters the deceased body, it steers him to establish a love around Diadorim. It is, precisely, this love that marks his surpassing of the father and the subversion of the superego order – which allows him to go beyond his pactary condition. It leads us to the statement that the structure of the Faustian pact allows articulating the advent of desire in its relationship with something that presents itself ―before‖ as destiny and that we can apprehend in the Freudian formula: Wo Es war, soll Ich werden.